El derecho a la protección de datos personales, igualdad y no discriminación y el libre acceso a la consulta de noticias del delito. - Sotomayor Calva, Diana Elizabeth (2023)
This research paper addresses the crossroads between the right to the protection of personal data, equality and non-discrimination, and free access to the consultation of crime news. It analyzes how the disclosure of crime-related information in digital media can affect the privacy and equality of individuals. It examines the application of legal and ethical standards to ensure the proper treatment of personal data in the context of media coverage of crime, considering both the individual's right to information and the need to protect dignity and avoid discrimination. The project seeks to identify possible challenges and solutions to achieve a balance between access to information, respect for privacy and the promotion of equality in a constantly evolving digital environment. This work aims to analyze the complex interaction between the right to the protection of personal data, the principles of equality and non-discrimination, and free access to crime-related news in the contemporary digital context. Through an interdisciplinary approach that combines qualitative and quantitative methods, it seeks to critically examine how access to information about crimes in digital media can impact the privacy, equality and non-discrimination of the individuals involved. It will be based on a solid theoretical framework that explores the legal and ethical bases of these three fundamental concepts: the right to the protection of personal data, equality and non-discrimination, and access to information. A content analysis of online crime news will be conducted to understand how personal data is presented and treated on the virtual platform of the State Attorney General's Office. The project aims to identify specific challenges and opportunities to improve personal data protection and promote equality in the dissemination of crime news. It addresses a crucial intersection in the digital age, exploring the complex dynamics between personal data protection, equality and non-discrimination, and free access to crime news. The present research is non- experimental and descriptive, it is proposed under a mixed approach, qualitative by the bibliographic review and quantitative by the statistical analysis of the information, the methods applied are: inductive-deductive, dogmatic, analytical-synthetic, comparative and historical- logical. Finally, we will use the techniques of bibliographic review, file and a survey conducted to judges, lawyers of the canton Macará on the right to the protection of personal data, equality and non-discrimination. Additionally, simple random sampling will be used for the statistical part.